The Coach’s Role And Efficiency In Selecting Half Long Distance Runners In Algeria (field Study On Half Long Distance Trainers In Algeria) - Almani , Imene; Chalroum , Abderrahmen (sports creativity, 2025)
The purpose of this study is to inform about the selection of the athletes in general and the runners of the half long distance in Algeria in a particular. Select the axial role that the coach plays in his selection, also, the necessary awareness that he does with a scientific methodology and a planning study which includes all the sides of the athletics activities practiced to choose the best idol in order to get the higher degree of level. Therefore, the researcher of this study based on the analytical descriptive methodology in a sample, which is consisted of 30 coaches activity in Algeria, uses the questionnaire forms and appropriate statistic means, furthermore, the most important result in this study is the philosophy of the runners of the half long distance in Algeria is still far away from the scientific form, and sometimes it has undergone at random. Whereas, it is considered as one of the most important pillar for the training process to the coach, and to the sport system in general. Furthermore, this is the best chosen myriad Algerian raw materials that will be guided to the best place.